Portable accelerometers for the evaluation of spatio-temporal gait parameters in people with Parkinson's disease: an integrative review. - de Oliveira Gondim, Ihana Thaís Guerra; de Souza, Caroline de Cássia Batista; Rodrigues, Marco Aurélio Benedetti; Azevedo, Izaura Muniz; de Sales Coriolano, Maria das Graças Wanderley; Lins, Otávio Gomes (Archives of Gerontology & Geriatrics, 2020)
• Smarthphone-based sensors have shown to be an interesting alternative in healthcare settings, not only for the assessment of spatio-temporal gait parameters in Parkinson's disease but also as an adjunct tool in gait rehabilitation. • Portable accelerometers when compared to conventional gait analysis methods showed the following advantages: lower cost; portability, and less complexity of reading for non-specialized users. • One disadvantage lies in the fact that portable devices still seem to show reduced precision and accuracy, with greater susceptibility to noise and external factors, when compared to conventional gait analysis methods usually performed in specialized laboratories. The progression of Parkinson's disease causes an increase in motor dysfunctions, which makes it necessary to evaluate and monitor these changes. This integrative review aimed to gather studies – without any language restrictions – on the use, advantages and disadvantages of portable accelerometers for the evaluation of spatio-temporal gait parameters in people with Parkinson's disease published between 2014 and 2019. Articles were selected from the PubMed, Web of Science and Science Direct databases by combining descriptors from the Health Sciences Descriptors (DeCS) and Medical Subject Headings (MeSH) – "accelerometry", "accelerometer", "ActiGraph", "gait", "gait analysis", "gait rehabilitation", "walking inertial sensors", "Parkinson disease", "Parkinson" and "Parkinson's disease" – using OR and AND. The adapted Critical Appraisal Skill Program was used to analyze the methodological quality. All the studies used portable wearable and wireless triaxial accelerometers. Among all types of accelerometers discussed, commercial wearable devices not based on smartphones and prototypes of wearable devices based and not based on smartphones can be pointed out. There was no standardization for the protocols of use, but the sensors were more often attached to the lower back (L3/L4/L5 vertebrae). The advantages included lower cost, possibility of use in outdoor environments and less complexity of data reading for non-specialized users. However, they still seem to show reduced precision and accuracy. Due to the still insufficient number of articles published on the subject, we consider the need for further research, which should detail protocols of evaluation, advantages and disadvantages in stages of disease.